Methyl esters (biodiesel) from Melanolepis multiglandulosa (alim) seed oil and their properties. Issue 2 (4th March 2019) - Knothe, Gerhard; Razon, Luis F.; de Castro, Maria Ellenita G.
ABSTRACT: Sufficient supply of feedstock oils is a major issue facing biodiesel production. In this work, methyl esters, also known as biodiesel, of the seed oil of Melanolepis multiglandulosa, a member of the Euphorbiaceae family, were prepared using standard conditions, with sodium methoxide as catalyst, and characterized regarding their fuel properties in relation to biodiesel standards. Melanolepis multiglandulosa methyl esters generally meet the requirements of biodiesel standards, with cold flow (cloud point of 5°C) likely being the major technical issue to resolve.